The effect of schema therapy and schema-focused mindfulness therapy on marital communication of Iranian women in Malaysia - Nooroney, Nooshin; Wan Jaafar, Wan Marzuki; Hassan, Siti Aishah; Noah, Sidek Mohd (Konselor, 2019)
The aim of this study is to evaluate the effectiveness of schema therapy and schema-focused mindfulness therapy on marital communication among Iranian married women who lived in Malaysia from ‎2015 to 2016. The qualified participants were assigned randomly into three groups, i.e. two experimental groups which in order received schema therapy and schema-focused mindfulness therapy, and a control group which did not receive any treatment. The treatment sessions lasted nearly three months using marital satisfaction subscale from the ENRICH questionnaire, a demographic questionnaire and Young's schema questionnaire as the instruments. Two-way repeated measures ANOVA and ANCOVA were also employed for data analysis. The findings of the study revealed that schema therapy and schema-focused mindfulness therapy had a significant effect on marital communication of Iranian women in Malaysia. Moreover, the findings showed more improvement for schema-focused mindfulness therapy group at two months follow-up.